1992
DOI: 10.1111/j.1471-4159.1992.tb09766.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging Produces a Specific Pattern of Striatal Dopamine Loss: Implications for the Etiology of Idiopathic Parkinson's Disease

Abstract: To examine the possible causal contribution of normal or accelerated aging to the neurodegenerative process of Parkinson's disease, we measured the influence of aging on subregional striatal dopamine and homovanillic acid levels in postmortem brain of 23 neurologically and psychiatrically normal human subjects 14-92 years old. We observed a significant decline in striatal dopamine levels and increase in the homovanillic acid/dopamine molar ratios with increasing age. The dopamine loss, on average, was of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
142
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(156 citation statements)
references
References 48 publications
13
142
1
Order By: Relevance
“…They thus provide further contrary evidence for the older doctrine-derived from both autopsy studies of PD [4] and early animal lesion studies [33]-that a depletion of striatal dopamine in excess of 80% was necessary for functional impairment to occur. Kish et al [24] have extrapolated that, in normal aging, this threshold would only be reached at about the age of 110 years. Our results demonstrate, on the contrary, that among healthy subjects of retirement age with no clinical evidence of PD, diminished nigrostriatal dopaminergic function is associated with slowing of reaction speed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They thus provide further contrary evidence for the older doctrine-derived from both autopsy studies of PD [4] and early animal lesion studies [33]-that a depletion of striatal dopamine in excess of 80% was necessary for functional impairment to occur. Kish et al [24] have extrapolated that, in normal aging, this threshold would only be reached at about the age of 110 years. Our results demonstrate, on the contrary, that among healthy subjects of retirement age with no clinical evidence of PD, diminished nigrostriatal dopaminergic function is associated with slowing of reaction speed.…”
Section: Resultsmentioning
confidence: 99%
“…Our failure to detect a significant correlation between striatal DAT availability and CVLT learning strategy in our healthy elderly subjects may be a consequence of inadequate statistical power. Alternatively, it may reflect the qualitative difference between the disease process of PD and the normal aging of the nigrostriatal dopaminergic system that has been suggested by previous postmortem [24] and neuroimaging [44] studies.…”
Section: Relationship To Other Preclinical and Clinical Studiesmentioning
confidence: 94%
“…The intact striatum was used as an internal control condition for each animal. Although tracers binding to VMAT2 such as DTBZ are not specific for the dopaminergic terminals alone, 90% of monoaminergic innervation in the striatum is of dopaminergic origin (Kish et al, 1992), thus making DTBZ an ideal tracer to assess lesion severity (LS) in a unilateral model of PD. Indeed, a previous study has shown a significant correlation between PET binding measures and post-mortem autoradiographic measurements using the racemic form of this tracer ([ 11 C](7) dihydrotetrabenazine) (Strome et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, damage to this enzyme can cause serious clinical consequences. Indeed, the decreased activity of COX has been found in a variety of neurodegenerative illnesses such as Parkinson′s disease and Alzheimer′s disease [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, damage to this enzyme can cause serious clinical consequences. Indeed, the decreased activity of COX has been found in a variety of neurodegenerative illnesses such as Parkinson′s disease and Alzheimer′s disease [1][2][3].Accumulated evidence indicates that mitochondria are vulnerable to ethanol/EW toxicity. Reactive oxygen species produced during ethanol metabolism altered mitochondrial function in rodents [4,5].…”
mentioning
confidence: 99%